2021
DOI: 10.3390/ijerph18158033
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Noise Exposure and Associated Health-Risk Behavior in Adolescents: An Explanatory Study among Two Different Educational Programs in Flanders

Abstract: Adolescents frequently engage in noisy leisure activities which can result in hearing-related problems. However, the effect of leisure noise exposure is liable to an individual’s risk-taking behavior. Identifying leisure noise activities and relevant factors related to risk-taking behavior in adolescents, are important to optimize hearing conservation programs targeting youngsters. The purpose of the study was to explore the presence of hearing-related symptoms, as well as noise exposure during various activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…Since they spend a significant amount of time in educational institutes, uncontrolled noise exposure will cause them to develop premature NIHL symptoms. With a low level of awareness and poor hearing protection practices, the risk of ear damage among them can be high [ 30 , 31 , 32 , 33 ]. One of the educational institutions in Malaysia that is particularly at risk of exposing students to noise is the Technical and Vocational Education and Training (TVET) Institution [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since they spend a significant amount of time in educational institutes, uncontrolled noise exposure will cause them to develop premature NIHL symptoms. With a low level of awareness and poor hearing protection practices, the risk of ear damage among them can be high [ 30 , 31 , 32 , 33 ]. One of the educational institutions in Malaysia that is particularly at risk of exposing students to noise is the Technical and Vocational Education and Training (TVET) Institution [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study found although over 70% of cohorts were advised to wear HP, usage rates at concerts ranged from 11.3% to 24.7%. 22 Participants cited discomfort, inconvenience, and poor sound quality as primary reasons for not using HP. 22 Similarly, we found many respondents cited discomfort (25.38%), inconvenience (22.11%), and impact on music quality (32.46%) as reasons for not wearing HP.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing awareness and education alone, however, may not effectively prevent recreational NIHL. One study found although over 70% of cohorts were advised to wear HP, usage rates at concerts ranged from 11.3% to 24.7% 22 . Participants cited discomfort, inconvenience, and poor sound quality as primary reasons for not using HP 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about possible individual barriers to the acceptance of such interventions and about how they can be addressed through communication. So far, studies on attitudes and beliefs towards hearing protection have focused mostly on personal listening devices [ 16 , 17 , 18 , 19 ], while only a few studies have investigated factors associated with attitudes towards preventive measures in venues [ 20 ].…”
Section: Introductionmentioning
confidence: 99%